Critical Path Method dan Algoritma Genetika untuk Optimasi Durasi dan Biaya Pembangunan - Wahdania A.T. Ja’a; Muhammad Rifai Katili; Djihad Wungguli; Nisky Imansyah Yahya (Universitas Negeri Gorontalo, 2022)
A large project requires proper scheduling to obtain the duration of development and costs incurred more optimally. Optimization is submitting the project duration efficient solution by using various alternatives that can be reviewed in terms of cost and time. Optimization problems can be solved using operating research. Selected Critical Path Method and Genetic Algorithm as a compelling method for planning and an methods rolling schedules the Critical Method because this method considers the assumption of time, then the implementation of the project is done without thinking about resources and can also determine when an activity starts and when the end of the project. While the Genetic Algorithm method is a method that can provide quick and efficient results in forming a project schedule. Based on the results of the study obtained that has managed to get the optimization value by minimizing the duration of the project using CPM (Critical Path Method) is 199 days from the total project time of the construction of the health center Biau 210 working days. and the costs incurred due to the optimization using genetic algorithms amounted to Rp. 231,515,082 from the initial cost of the project of Rp.382,784,000.